2013
DOI: 10.1111/jhn.12061
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intake and dietary sources in a representative sample of Spanish adults

Abstract: Background: Vitamin D plays an essential role in bone mineralisation and its deficiency is associated with several chronic diseases. Some studies have reported a deficient status of vitamin D in Spanish and European population. The present study aimed to assess vitamin D intake, dietary sources of this nutrient and its adequacy with respect to the dietary reference intakes (DRI) in a representative sample of Spanish adults. Methods: Four hundred and eighteen adults (aged 18-60 years) from 15 Spanish provinces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In Spain and Australia, some of the fluid milks on the market are fortified with vitamin D and studies conducted in these countries among the adult population showed that the contribution of milk to total vitamin D intake was 15–18%, with total intakes being 3.5 and 4.4 µg/day, respectively [ 16 , 17 ]. In a Canadian population-based study among adults, the total vitamin D intake was shown to be 5.6 µg/day among females and 4.8 µg/day among males, and milk contributed 48% of the total vitamin D intake among females and 63% among males [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain and Australia, some of the fluid milks on the market are fortified with vitamin D and studies conducted in these countries among the adult population showed that the contribution of milk to total vitamin D intake was 15–18%, with total intakes being 3.5 and 4.4 µg/day, respectively [ 16 , 17 ]. In a Canadian population-based study among adults, the total vitamin D intake was shown to be 5.6 µg/day among females and 4.8 µg/day among males, and milk contributed 48% of the total vitamin D intake among females and 63% among males [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, fluid milks can be fortified with vitamin D by around 1 µg/100 g; the fortification is not mandate at the federal level, but most states mandate fortification [ 12 ]. In other countries, such as United Kingdom, Ireland, Spain, and Australia, the fortification is not systematic, but there is a varying number of vitamin D-fortified milk products available [ 13 , 14 , 15 , 16 , 17 ]. However, data on their proportion to the total amount of dairy products in different countries is not easily accessed due to fluctuations in the market.…”
Section: Introductionmentioning
confidence: 99%
“…The production of vitamin D in the skin is the most important source of vitamin D and depends on the intensity of UV irradiation and exposure. Vitamin D can also be provided to a small extent in the diet, being mainly present in fish oils and fortified dairy products [ 52 ].
Fig.
…”
Section: Hormonal Factors That Affect Pi Balancementioning
confidence: 99%
“…Fish, egg yolk, cheese, and mushrooms are the only dietary sources that contain natural vitamin D (12). Among these, fish has, in general, the highest content of vitamin D (12,13) and is the major natural food source in many populations within (14)(15)(16)(17) and outside of (18,19) Europe. Other significant food sources are fortified items such as margarine, skimmed milk, and orange juice (20,21).…”
Section: Introductionmentioning
confidence: 99%